Review of Amnesia & Friends, Stereo Miru, Item 9; Crystal Palace: Inside, Outside, Eddie Prevost Band; Miru: Long & Short One, Robert Carter: Do Not Cover, and Chamberpot - Roberts, David (Contact: A Journal for Contemporary Music (1971-1990), 1978)